Research on the Risk Management of Loan Concentration in Chinese Commercial Banks - Chu, Panyun (2020)
Commercial banks may have loan concentration when lending because it is a very common phenomenon in the process of economic development. To some extent, appropriate loan concentration has a positive impact on economic development, but excessive loan concentration will have adverse effects on the national economy, the operating efficiency and risk control of commercial banks.This paper selects some relevant data of 10 representative commercial banks from 2011 to 2018 to study the impact of loan concentration on the risk and income of Chinese commercial banks by quantitative analysis.This article selects relevant data from 10 representative commercial banks from 2011 to 2018 and studies the impact of loan concentration on risks and returns.